PENGARUH PENERAPAN E-FILING DAN PEMAHAMAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DI KPP PRATAMA PEKANBARU TAMPAN - Dermawan, Deni; Makhdalena, Makhdalena; RM. Riadi, RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to see and analyze the influence of e-filing and understanding of taxation on taxpayer compliance both simultaneously and partially on taxpayers registered at the KPP Pratama Pekanbaru Tampan. The population in this study were individual taxpayers registered at KPP Pratama Pekanbaru Tampan as many as 169,059 people, while in determining the measurement of samples using Solvin formula amounted to 100 people. Data analysis techniques used regression with the help of SPSS. The results showed that the application of e-filing and understanding of taxation had a positive and significant effect on tax compliance both partially simultaneously.Key Words: Application of e-filing, Understanding of Taxation, Compliance of Taxpayers